Microwave ablation for painful chest wall metastases from gastrointestinal stromal tumor: a case report - Wang, Shishi; Wang, Lu; Li, Tingting; Li, Yuan; Zhuang, Min; Lu, Man (Frontiers in Oncology, 2024)
Background: Gastrointestinal stromal tumor (GIST) is the most common mesenchymal tumor of the digestive tract, with the potential to metastasize. Metastases to bone and soft tissue are more frequent in advanced cases, where targeted therapy is the standard treatment. However, around 10-15% of patients develop disease progression despite treatment. Studies have shown the efficacy of ablation in managing bone and soft tissue metastases (1 -2), but there are no reports of ablation for treating GIST bone or soft tissue metastases.Case presentation: In 2022, a 58-year-old man complaining of left back pain was admitted to Sichuan Cancer Hospital. He had undergone radical resection of the primary gastric GIST and vertebral metastases in 2014 and 2018, respectively. In 2019, rib metastases still occurred despite the use of targeted therapy. During the course of radiotherapy, targeted therapy, and immunotherapy, he experienced persistent chest wall pain. In addition, new lesions occurred in the lungs and chest wall in 2022. After a thorough assessment, microwave ablation (MWA) was recommended in response to his demand for immediate pain relief. The large rib metastasis constricted the spleen, so we completed the ablation in two sessions to reduce the risk of complications. He had 17 months of follow-up until September 2023, during which time his discomfort was considerably reduced.For GIST patients with soft tissue and bone metastases, MWA may offer substantial immediate pain alleviation. When other treatment procedures fail to achieve adequate efficacy, it provides an option.